METODE DAKWAH DALAM MENINGKATKAN SEMANGAT BERIBADAH JAMIYYAH YASIN AL AZZAM DESA KEBONDALEM - MASKUR, MASKUR; KARIMAH, ULA MASYRIFATUL (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research is motivated by the problem of less than optimal community worshipactivities, especially women who are already married in Kebonrejo Hamlet, KebondalemVillage, Bangorejo District, Banyuwangi Regency. So that Jamiyyah Yasin Al Azzamcarried out various da'wah methods to increase the spirit of worship in accordance withgood and correct sharia in the people of Kebonrejo Hamlet, especially housewives. Theproblem in this study is what is the da'wah method carried out by Jamiyyah Yasin Al Azzamin increasing the spirit of worship of the women of Kebonrejo Hamlet, Kebondalem Village,Bangorejo District, Banyuwangi Regency. The location of the research is Jamiyyah YasinAl Azzam in Kebonrejo Hamlet, Kebondalem Village, Bangorejo District, BanyuwangiRegency. The type of research is descriptive with a qualitative approach. The researchinformants amounted to 7 (seven) people using data collection techniques throughobservation, interviews and documentation. From the results of this study, it can beconcluded that the da'wah method applied by Jamiyyah Yasin Al Azzam to increase thespirit of worship of women in Kebonrejo Hamlet, Kebondalem Village, Bangorejo District,Banyuwangi Regency is: First, the method of da'wah bil hikmah; second, the da'wahmethod of bil mauidzah hasanah; third, the method of oral da'wah bil; and fourth, themethod of da'wah bil hal.